Safety Use Of Personal Protective Equipment (PPE) to Anxiety During The Covid-19 Pandemic On Nurses - Heru Suwardianto; Lilik Setiawan; Andika Siswoariwibowo; Teguh Santoso (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The research method uses a Cross Sectional Design. The sample size obtained was 557 respondents. The variable measurement instrument uses a questionnaire on google form. Research has obtained ethical clearance. Data analysis using spearman-rho with a <0.05. The results showed that the majority of respondents were female (70.4%). Most respondents are 36-45 years old (39.5%). Respondents all worked as nurses and most of the respondents worked < 5 years (26.9%). The results of the study obtained 12% who stated that it was not so safe in the use of PPE, and there were 3.5% who stated that it was not safe to use PPE. The results showed that p= 0.001 with a <0.05, which means there is a significant relationship between the safety of using PPE on anxiety, with a correlation coefficient of 0.407 which means it has a fairly close relationship between the safety of using PPE on anxiety